The Advance of CRISPR-Cas9-Based and NIR/CRISPR-Cas9-Based Imaging System - Qiao, Huanhuan; Wu, Jieting; Zhang, Xiaodong; Luo, Jian; Wang, Hao; Ming, Dong (Frontiers in Chemistry, 2021)
The study of different genes, chromosomes and the spatiotemporal relationship between them is of great significance in the field of biomedicine. CRISPR-Cas9 has become the most widely used gene editing tool due to its excellent targeting ability. In recent years, a series of advanced imaging technologies based on Cas9 have been reported, providing fast and convenient tools for studying the sites location of genome, RNA, and chromatin. At the same time, a variety of CRISPR-Cas9-based imaging systems have been developed, which are widely used in real-time multi-site imaging in vivo. In this review, we summarized the component and mechanism of CRISPR-Cas9 system, overviewed the NIR imaging and the application of NIR fluorophores in the delivery of CRISPR-Cas9, and highlighted advances of the CRISPR-Cas9-based imaging system. In addition, we also discussed the challenges and potential solutions of CRISPR-Cas9-based imaging methods, and looked forward to the development trend of the field.